Taxing Times: Inter-Criminal Victimization And Drug Robbery Amongst The English Professional Criminal Milieu. Issue 1 (2nd January 2020) - Treadwell, James; Ancrum, Craig; Kelly, Craig
ABSTRACT: This article considers the oft-hidden instances of inter-criminal victimization in illegal drug markets amongst serious criminals in the North of England. Focusing on proto-criminal activity known in regional argot as 'taxing' (drug dealers robbing one another) it draws on ethnographic material and suggests that contrast to the literature on the subject from the USA 'taxing' in England rarely leads to cycles of retaliatory violence. Yet against a more general climate of precariousness in disadvantaged communities in England, 'taxing' as a deviant behavior is a gainful, relatively low-risk activity for a minority of established, professional violent criminals.